Association of Risk of Dementia With Direct Oral Anticoagulants Versus Warfarin Use in Patients With Non-valvular Atrial Fibrillation: A Systematic Review and Meta-analysis. Issue 1 (January 2021) - Lee, Zong Xuan; Ang, Eshen; Lim, Xin Tian; Arain, Salman Javed
Abstract : Abstract: Atrial fibrillation (AF) is associated with an increased risk of dementia. Studies have shown the beneficial effects of anticoagulants in preventing dementia in this population. However, evidence around the use of direct oral anticoagulants (DOACs) versus warfarin in AF-related dementia prevention remains sparse. This systematic review and meta-analysis aimed to evaluate the use of DOACs versus warfarin in dementia prevention in this population. MEDLINE, EMBASE, PsycINFO, and the CENTRAL databases were systematically searched from its inception until May 2020. Nine studies (n = 611, 069) were included for quantitative meta-analysis. DOACs use was associated with a lower risk of composite dementia outcomes compared with warfarin use [odds ratio (OR) 0.56, 95% confidence interval (CI) 0.34–0.94, P = 0.03]. No significant difference was found in subtypes of dementia (vascular dementia, Alzheimer's disease, and cognitive disorder) between both groups. No significant difference in the risk of composite dementia outcomes between the dabigatran and warfarin groups (OR 0.97, 95% CI 0.88–1.08, P = 0.61). Apixaban (OR 0.58, 95% CI 0.50–0.67, P < 0.00001) and rivaroxaban (OR 0.67, 95% CI 0.61–0.75, P < 0.00001) use were both associated with a significantly lower risk of composite dementia outcomes compared with warfarin use. Findings need to be interpreted with caution because of low certainty of evidence. In conclusion, this systematic review and meta-analysis of 9 comparative studies demonstrated the superiority of DOACs over warfarin in prevention of dementia in AF. Future prospective trials with adequate follow-up period are warranted to ascertain its causal relationship. Abstract : Supplemental Digital Content is Available in the Text.